Angiotensin II-superoxide-NFκB Signaling and Aortic Baroreceptor Dysfunction in Chronic Heart Failure - Zhang, Dongze; Muelleman, Robert L.; Li, Yulong (Frontiers in Neuroscience, 2015)
Chronic heart failure (CHF) affects approximately 5.7 million people in the United States. Increasing evidence from both clinical and experimental studies indicates that the sensitivity of arterial baroreflex is blunted in the CHF state, which is a predictive risk factor for sudden cardiac death. Normally, the arterial baroreflex regulates blood pressure and heart rate through sensing mechanical alteration of arterial vascular walls by baroreceptor terminals in the aortic arch and carotid sinus. There are aortic baroreceptor neurons in the nodose ganglion (NG), which serve as the main afferent component of the arterial baroreflex. Functional changes of baroreceptor neurons are involved in the arterial baroreflex dysfunction in CHF. In the CHF state, circulating angiotensin II (Ang II) and local Ang II concentration in the NG are elevated, and AT1R mRNA and protein are overexpressed in the NG. Additionally, Ang II-superoxide-NFκB signaling pathway regulates the neuronal excitability of aortic baroreceptors through influencing the expression and activation of Nav channels in aortic baroreceptors, and subsequently causes the impairment of the arterial baroreflex in CHF. These new findings provide a basis for potential pharmacological interventions for the improvement of the arterial baroreflex sensitivity in the CHF state. This review summarizes the mechanisms responsible for the arterial baroreflex dysfunction in CHF.